Use of Enzymatic Catalysis with Trichoderma sp., for Deinking of MOW Type Paper in Flotation Columns - Jeovani González P.; Ramiro Escudero G. (Chemical and Materials Sciences: Developments and Innovations Vol. 7, 2024)
Deinking, up to now, is generally carried out under alkaline conditions and requires the use of chemical reagents such as sodium hydroxide, hydrogen peroxide, sodium silicate, etc., to be more efficient in the process and obtain a product with specific optical properties. Sodium hydroxide (NaOH) is traditionally used to hydrolyze cellulose fibers, and to set the pH of the medium to values greater than 10, during deinking of MOW (Mixed Office Waste) type paper; however, substantial amounts of solid and liquid waste are created, and their management is problematic and dangerous. Recently, the implementation of biological treatments; for example, enzymatic deinking, is presented as an option to deink mixed office prints at neutral pH; that is, with the minimum use of chemical reagents and, therefore, better waste management and less environmental impact. The main objective of this research work is to study the mechanism of hydrolysis, detachment and ink capture in the bubble-enzyme-ink particle system, during the deinking of office paper-type MOW, using a laboratory column flotation. The cellulase enzyme Trichoderma sp. was used. The efficiency of deinking office paper using enzymes, and the traditional procedure using sodium hydroxide is compared. The quality of the deinked fibers by measuring their optical properties (whiteness, reflectance, opacity, black spots and tonality) was performed in the Laboratory of the Paper Industry Bio Papel Scribe SA de CV, located in the city of Morelia, Michoacán, México. The operational variables of the flotation column were established through experiments in the water-air system and by adding 100 ppm of pine oil as a surfactant (surface tension of the liquid in 56.6 dynes /cm). The superficial air flowrate was set at 1.27 cm /s (6 LPM), whereas the pulp feed flow rate was 0.88 cm /s. For each deinking procedure samples were collected from the tailings stream (deinked fiber), with standard laboratory sheets, conforming to the standard TAPPI T-205-OM-81, to which the optical properties were determined: ISO whiteness (Brightness), Factor of Reflectance, Opacity and Tonality. The experimental results show the feasibility of recycling MOW-type office paper by using the enzyme cellulase Endo-\(β\)-1,4-D-glucanase and the amino acids Aspartate, Glutamate and Asparagine; the latter, individually and mixed. The optical properties of the sheets of paper formed with the cellulose deinked by this procedure were better than those evaluated to sheets of paper formed with fibers of recycled and deinked paper by the traditional procedure. In the case of the combined use of the three amino acids, the ISO whiteness is 90.8%, 303.4 ppm of black spots, reflectance of 47.1% and 89.5 of opacity. By the traditional procedure, the reported whiteness is 80.2%, the reflectance is 57.4%, and the opacity is 99.6%. From the paper deinking experiments using the conventional method with NaOH and enzymatic deinking with the help of the commercial enzyme Cellulase Trichoderma sp., it is concluded that the optical and physical properties in the fiber deinked by the conventional method are slightly better than those obtained in the fiber deinked with the enzyme cellulase; however, the weight ratio between the enzyme and the MOW paper should be varied to establish the possibility of improving the optical characteristics of the deinked fibers with this enzyme, until reaching optical properties greater than the deinked with NaOH.